ANALISIS TINGKAT KEBAHAGIAN MAHASISWA JURUSAN PENDIDIKAN AGAMA KRISTEN - Limmarten Simatupang (Institut Agama Kristen Negeri Tarutung, 2020)
This study aims to find out to what extent of the percentage analysis of the level of students’ happiness in their life processes. The research method used is descriptive quantitative and inferential research. The population of this study were all students of the department of Christian religious education IAKN Tarutung which were 566 students. The sample in the study was 86 people who were randomly assigned. The research instrument was a closed questionnaire with four options. Data analysis techniques using the t-test. Based on the analysis it is known that the level of student happiness is 78.45% in the good category. From the results of the hypothesis test that the t-test = 13.251 and the table is 1.684, where t-count t-table is 13.2511.684. Thus it can be concluded that the analysis of the happiness level of department PAK IAKN Tarutung students in 2019 in their life processes is ≥ 75% of what was expected.BAHASA INDONESIA ABSTRACT: Penelitian ini bertujuan untuk mengetahui seberapa besar persentase analisis tingkat kebahagiaan mahasiswa dalam proses kehidupannya. Metode penelitian yang dipakai adalah penelitian kuantitatif deskriptif dan inferensial. Populasi penelitian ini adalah seluruh mahasiswa Jurusan PAK IAKN Tarutung sebanyak 566 orang. Sampel dalam penelitian 86 orang yang ditetapkan secara acak. Instrumen penelitian ini berupa angket tertutup dengan empat option. Teknik analisis data dengan menggunakan uji t. Berdasarkan hasil analisis diketahui bahwa tingkat kebahagiaan mahasiswa adalah 78,45 % berada dalam kategori baik; Dari hasil uji hipotesa bahwa uji thitung = 13,251 dan ttabel yaitu 1,684, dimana thitung ttabel yaitu 13,2511,684. Dengan demikian dapat disimpulkan bahwa hasil penelitian ini menunjukkan bahwa analisis tingkat kebahagiaan mahasiswa Jurusan PAK IAKN Tarutung Tahun 2019 dalam proses kehidupannya adalah ≥ 75 % dari yang diharapkan.Keywords: Happiness; student college; Christian education